2023
DOI: 10.1186/s13054-022-04297-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of corticosteroids in cardiac arrest: a systematic review, meta-analysis and trial sequential analysis of randomized control trials

Abstract: Background Post-cardiac arrest, outcomes for most patients are poor, regardless of setting. Many patients who do achieve spontaneous return of circulation require vasopressor therapy to maintain organ perfusion. There is some evidence to support the use of corticosteroids in cardiac arrest. Research question Assess the efficacy and safety of corticosteroids in patients following in- and out-of-hospital cardiac arrest. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…More recently, randomized clinical trial on 512 patients of 10 hospitals in Denmark showed significant increase in probability of return of spontaneous circulation (ROSC) in patients receiving combined treatment of methylprednisolone and vasopressin in comparison to patients receiving placebo. However, there was no difference in 30-days mortality and neurological outcome of the patients [262].…”
Section: Steroids and Vasopressin Treatment In Cardiovascular Diseasesmentioning
confidence: 77%
“…More recently, randomized clinical trial on 512 patients of 10 hospitals in Denmark showed significant increase in probability of return of spontaneous circulation (ROSC) in patients receiving combined treatment of methylprednisolone and vasopressin in comparison to patients receiving placebo. However, there was no difference in 30-days mortality and neurological outcome of the patients [262].…”
Section: Steroids and Vasopressin Treatment In Cardiovascular Diseasesmentioning
confidence: 77%
“…Glucocorticoids have abundant anti-inflammatory properties and thereby may improve patient outcomes following OHCA [ 17 ]. Norepinephrine is often a first-line vasoactive agent used in the management of hemodynamic instability following cardiac arrest [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As increasingly used since the COVID-19 epidemic ( 18 , 33 , 34 ), IL6 may help more accurately to diagnose VAP occurring within 48 hours after sampling in cardiac arrest patients in addition to usual biomarkers such as CRP. Finally, some postcardiac arrest patients experiencing a major inflammation even if triggered by VAP, confirmed by an important increase in inflammatory biomarkers, may potentially benefit from steroids or IL6 receptor antibodies besides antibiotics ( 31 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%